Student’s Engagement in School: Conceptualization and relations with Personal Variables and Academic Performance - Veiga, Feliciano Henriques (2015)
This article reviews the literature regarding Student’s Engagement in School (SES), its relationship with personal variables, as well as with academic performance. Although SES’ conceptualization may vary across studies, there is general agreement concerning the multidimensional nature of this construct, encompassing three dimensions – cognitive, affective and behavioural. It is seen as an antecedent of several required outcomes, at academic level, but also as a valorous construct itself, both as mediator and product. More particularly, this concept has been the focus of debate concerning academic success and school dropout. There can also be found a significant number of studies which suggest that personal (self-efficacy, self-concept), as well as contextual (peers, school, family) factors are related with school engagement; additionally, the lack of engagement is linked with low academic performance, behavioural problems and school dropout. Thus, Student’s Engagement in School is perceived as a potentially effective response to the problems affecting schools and their students, and an aspect to be considered in preventing problematic patterns related to scholary contexts.